Decolourization of methyl orange in UV assisted fenton-like reaction using Fe-MKSF catalyst / Nur Hidayati Abdullah - Abdullah, Nur Hidayati; Zubir, Nor Aida; Hassan, Hamizura (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
In this work, two types montmorillonite clay (MKSF and MK10) were applied as catalyst support in heterogeneous UV assisted Fenton-like reaction. MKSF was chosen for the iron immobilization based on catalytic activity performance. Fe-supported montmorillonite KSF (Fe-MKSF) exhibited both increment in surface area, 175.208 m2 /g and pore volume, 0.3536 cm3 /g compared to the pristine MKSF as a result of incorporation of iron species onto MKSF matrix. The reactivity of Fe-MKSF was further tested on the effect of UV irradiation. Fe-MKSF exhibited 99% of methyl orange (MO) removal within 45 min of reaction under UVC illumination but it takes more than 120 min under UVA illumination. These findings proved Fe-MKSF as a promising alternative catalyst in decolourization of recalcitrant contaminant in wastewater.